Parish Priesthood of the Don Host Region: Features of the Formation of the Social Status and Its Change Between the Mid 17th and the Early 20th Century - Alla V. Shadrina (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2019)
Introduction. This article deals with a pressing problem of historical science: the analysis of the social status of the parish priesthood in the South of Russia, and its transformations on the example of the Don Host region.